Factors affecting postmusculoskeletal tumour surgery wound problem treatment with negative pressure wound therapy - AKGÜLLE, AHMET HAMDİ; EROL, BÜLENT; ŞİRİN, EVRİM (WILEY, 2020)
The aim of the study is to investigate the risk factors identified in literature that have been associated with prolonged Negative Pressure Wound Therapy (NPWT). Our study included patients who developed local wound problems after bone or soft tissue sarcoma surgery with negative margin at our clinic between 2012 and 2018 and treated with NPWT. All patients were followed up of at least 6 months. Sex, albumin level, skin infiltration, type of wound problem, postoperative intensive care unit (ICU) requirement, and intraoperative blood loss were found to be influential factors on NPWT > 10 sessions. We conclude that treatment may be prolonged and the necessary precautions need to be taken in patients with an impaired preoperative nutritional condition, with intraoperative high amount of blood loss, and with long postoperative stays in the ICU as well as if the underlying cause for wound problem is an infection.
Keywords: musculoskeletal tumour surgery; negative pressure wound therapy; wound complication; SOFT-TISSUE SARCOMA; VACUUM-ASSISTED CLOSURE; RISK-FACTORS; COMPLICATIONS; EXTREMITY; INFECTION; RESECTION